The hidden history that winds through every city Critical Urban Studies, Social Movements, and Radical Transformation - Pozzi, Giacomo; Madden, David (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2020)
Aim of this special issue of Tracce Urbane is to stimulate an exploration of the historical, political, social, and intellectual reasons that brought to a peculiar and, in a way, ambiguous field of knowledge: that of critical urban studies. David Madden, Professor in Sociology at the London School of Economics and Political Science, Co-Director of the Cities Programme, and co-author, with Peter Marcuse, of In Defense of Housing: The politics of crisis (Verso, 2016), whose Italian edition is forthcoming (by Barbara Pizzo for Edit Press), has been invited to discuss the complex social arena in which critical urban studies stands, reflects, and acts. In the conversation that follows, Madden explores some fundamental topics related to the production of this specific academic knowledge, such as the ‘canonlessness’ that characterizes urban studies, the emphasis on intervention and radical transformation that inhabits critical urban studies, the utopian dimension of this tradition of study, the heterogenous genealogies that should be considered when approaching this discipline, the necessity of listening and considering the social sources of critique that rise in every neighbourhood or city around the globe, the future of critical urban studies and its relation with urban struggle, the way in which social movements contribute to its development, the role of academics in promoting social changes, his personal commitment in defense of housing as a space for inhabitants. In his words we can find a first answer to Saskia Sassen’s argument that «spaces of the expelled cry out for conceptual recognition» (Sassen, 2014: p. 222). According to Madden, this recognition cannot be only conceptual. It must be grounded, it must be critical, it must be radical.